The Effect of Coronavirus Disease-19 Pandemic Lockdown and the Overlapping Ramadan Fasting Period on Glucose Control in Insulin-Treated Patients With Diabetes: A Flash Glucose Monitoring Study - Helal, Radwa; Ashraf, Tanveer; Majeed, Maria; Lessan, Nader (Frontiers in Nutrition, 2022)
Background A strict lockdown was enforced during COVID-19 pandemic in many countries including the UAE. Lockdown period overlapped with Ramadan which is accompanied by its own drastic changes in lifestyle. Aims We report the impact of COVID-19 lockdown (between 22/3/2020 and 24/6/2020) on glucose control pre- and post-lockdown during Ramadan, in patients with type 1 diabetes (T1D) and type 2 diabetes (T2D) on insulin therapy. Methods Twenty-four patients (19 males, 6 females) were monitoring their glucose levels using flash glucose monitoring (FGM), remotely connected to the diabetes clinic in Imperial College London Diabetes Centre (ICLDC), Abu Dhabi, UAE were included. Using the international consensus on use of continuous glucose monitoring guidelines (1); analyses of data were performed on glucose management indicator (GMI), time in range (TIR), time in hyperglycaemia, time in hypoglycaemia, low blood glucose index (LBGI) and high blood glucose index (HBGI). Variables were calculated for each period: 30 days before lockdown 14/2/2020-14/3/2020; 30 days into lockdown and Pre-Ramadan 20/3/2020-18/4/2020; and 30 days into lockdown and Ramadan 24/4/2020-23/5/2020, using cgmanalysis package in R-studio software (2). Results Mean average glucose remained steady before and during lockdown, no significant differences observed in TIR, time in hypoglycaemia, and LBGI between pre-lockdown and lockdown. However, there was a statistically significant difference in GMI and percentage of time in hyperglycaemia (> 10.0 mmol/L) between Ramadan and pre-Ramadan during the lockdown period in p=0.007, 0.006, 0.004 respectively. Percentage of TIR (3.9-10.0 mmol/L) was significantly lower in Ramadan as compared to pre-Ramadan (50.3% v 56.1%; p= 0.026). Mean absolute glucose (MAG) (182.0 mmol/L v 166.6 mmol/L, p=0.007) and HBGI (10.2 (6.8, 14.8) v 11.9 (7.9, 17.8), p=0.037) were significantly higher in Ramadan compared to pre-Ramadan period. There was no statistically significant difference in percentage of time in hypoglycaemia (< 3.9 mmol/L) and LBGI between Ramadan and pre-Ramadan periods. Conclusion The lockdown period had no significant effects in markers of glycaemic control in the population studied. However, Ramadan fasting period embedded within this time was associated with several changes including increase in GMI, HBGI and glycaemic variability similar to what has been reported in other Ramadan studies.